2017
DOI: 10.1038/ncomms15697
|View full text |Cite
|
Sign up to set email alerts
|

Water scarcity hotspots travel downstream due to human interventions in the 20th and 21st century

Abstract: Water scarcity is rapidly increasing in many regions. In a novel, multi-model assessment, we examine how human interventions (HI: land use and land cover change, man-made reservoirs and human water use) affected monthly river water availability and water scarcity over the period 1971–2010. Here we show that HI drastically change the critical dimensions of water scarcity, aggravating water scarcity for 8.8% (7.4–16.5%) of the global population but alleviating it for another 8.3% (6.4–15.8%). Positive impacts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
232
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 378 publications
(238 citation statements)
references
References 67 publications
3
232
0
3
Order By: Relevance
“…Previous studies on transboundary river basins identified clear evidence of the impacts of upstream water use to downstream water availability and water scarcity level (Al-Faraj and Scholz 2015, Munia et al 2016, Nepal et al 2014, Veldkamp et al 2017. It has already been found that 460 about 0.95-1.44 billion transboundary people are under stress because of local water use, while upstream water use increased the stress level by at least 1 percentage-point for 30-65 sub-basins, affecting 0.29-1.13 billion people (Munia et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on transboundary river basins identified clear evidence of the impacts of upstream water use to downstream water availability and water scarcity level (Al-Faraj and Scholz 2015, Munia et al 2016, Nepal et al 2014, Veldkamp et al 2017. It has already been found that 460 about 0.95-1.44 billion transboundary people are under stress because of local water use, while upstream water use increased the stress level by at least 1 percentage-point for 30-65 sub-basins, affecting 0.29-1.13 billion people (Munia et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has already been recognized that upstream water use has considerable impact on downstream water scarcity by some regional and global studies (Munia et al 2016, Nepal et al 2014, Scott et al 2003, Veldkamp et al 2017). When population (or withdrawal) grows, downstream countries eventually become more reliant on the water available from 50 upstream parts of a basin in order to satisfy their needs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current LHMs also lack dynamic trade-offs among irrigation water supply, flooding control and hydropower production, water competitions between upstream and downstream users (Munia et al, 2016;Veldkamp et al, 2017), and deficit irrigation and rainwater harvest . These processes are increasingly important for regional hydrological model simulation.…”
Section: Incorporating Regional Water Managementmentioning
confidence: 99%
“…Water scarcity has become a worldwide problem and its 25 intensity has even increased due to climate change and human activities, e.g. unsustainable land management and water management Veldkamp et al, 2017). This turns to a major constraint to our socio-economic development and a threat to livelihood in the world.…”
Section: Introductionmentioning
confidence: 99%